A new specimen of Agorophius pygmaeus (Agorophiidae, Odontoceti, Cetacea) from the early Oligocene Ashley Formation of South Carolina, USA. (15th June 2016) - Godfrey, Stephen J.; Uhen, Mark D.; Osborne, Jason E.; Edwards, Lucy E.
Abstract: The holotype partial skull of Agorophius pygmaeus (the monotypic form for both the genus Agorophius and the Family Agorophiidae) has been missing for approximately 140 years. Since the discovery of Agorophius pygmaeus, many additional taxa and specimens have been placed in the Family Agorophiidae, only to be reclassified and removed later. This has created confusion as to what is and what is not an agorophiid and a lack of clarity as to what characteristics delimit the Agorophiidae. A newly discovered skull of an agorophiid recently collected from an underwater cliff face of the Ashley River, South Carolina, USA, is assigned to Agorophius pygmaeus . It derives from the base of the Ashley Formation (early Oligocene). The new specimen consists of most of the skull and periotics, which are well preserved and described for the first time in an agorophiid. The new specimen provides an opportunity to diagnose the Agorophiidae and place the genus and species within the phylogenetic context of the early odontocete radiation in the Oligocene, along with other taxa such as the Ashleycetidae, Mirocetidae, Patriocetidae, Simocetidae, Waipatiidae, and Xenorophidae. Based on this new understanding, Agorophiidae are known with certainty only from the early Oligocene of South Carolina, with other undescribed, potential agorophiid specimens from the Oligocene of the North Pacific region (Japan, Mexico, and Washington State).